Effects of chronic alcohol consumption on DNA damage and immune regulation induced by the environmental pollutant dibenzo[a, l]pyrene in oral tissues of mice. (2nd October 2017) - Chen, Kun-Ming; Schell, Todd D.; Richie, John P.; Sun, Yuan-Wan; Zhang, Shang-Min; Calcagnotto, Ana; Aliaga, Cesar; Gowda, Krishne; Amin, Shantu; El-Bayoumy, Karam
ABSTRACT : Previously, we showed that oral application of the environmental pollutant dibenzo[ a, l ]pyrene (DB[ a, l ]P) induces oral tumors in mice. Thus, in the present investigation we examined the effect of alcohol on DB[ a, l ]P-induced DNA damage and immune regulation; we showed that alcohol (6.4% v/v in the diet, 35% of Calories) significantly enhanced the levels of (−)- anti - trans -DB[ a, l ]P-dA while decreased the levels of GSH in the mouse oral tissues. Analysis of RNA expression revealed that DB[ a, l ]P alone upregulates inflammatory genes while alcohol suppresses several markers of immune surveillance. Collectively, these results suggest that alcohol may enhance oral carcinogenesis induced by DB[ a, l ]P.